Erosion wear characteristics of cemented carbide for mud pulser rotor. (December 2021) - Zhang, Weiguo; Zhang, Shuai; Dai, Wenhao; Wang, Xueqi; Liu, Baochang
Abstract: Mud pulser is the most commonly used Measurement While Drilling(MWD) instrument for downhole data transmission to the surface. The rotor of the key component of the mud pulser is made of cemented carbide material. Under the action of high speed mud erosion containing solid phase, the rotor will produce erosion wear and reduce the quality of signal transmission. To explore the erosion wear mechanism of rotor carbide in mud containing solid phase particles, the influences of different erosion angles and different erosion abrasive sizes on the erosion wear properties of cemented carbides were studied by taking quartz sand as erosion abrasive. By means of surface profilometer, scanning electron microscope (SEM) and energy spectrum analysis (EDS), the erosion wear mechanism of cemented carbide was revealed. The experimental results show that the erosion wear rate increases gradually with the increase of erosion angle. When the erosion angle is 90°, the maximum average erosion rate of WC-5Co, WC-6Co and WC-10Co cemented carbides is 2.39%, 2.42% and 3.22%, respectively. With the increase of the abrasive particle size, the erosion wear rate of the material increases first and then decreases. When 100–200 um, the maximum average erosion rates of WC-5Co, WC-6Co and WC-10Co are 1.84%, 1.98% and 2.48%, showing a significant "particle size effect". At low erosion angle, the wear mechanism is furrow and cutting mark, while at high erosion angle, the wear mechanism is pit. The erosion wear mechanism of small particle size abrasives is that a large area of surface layer falls off in the erosion area. The erosion wear mechanism of large particle size abrasive is the material loss in the erosion pit in the erosion area. Highlights: The mass loss at low erosion angle is mainly the removal of Co due to plastic deformation. The mass loss at high erosion angle is mainly the removal of Co and the pits caused by the removal of WC. The erosion rate of cemented carbide increases first and then decreases with the increase of abrasive particle size.